Analysis of a vortex causing sea-effect snowfall in the western part of the Black Sea: a case study of events that occurred on 30–31 January 2012 - Yavuz, Veli; Deniz, Ali; Özdemir, Emrah Tuncay (Springer Science and Business Media LLC, 2021)
In this study, snow events in the Marmara region were identified for the 2009–2018 period, and then the times at which a vortex causing the formation of a sea-effect snow (SES) band was seen over the Black Sea were determined from Terra, MSG-2 and MSG-3 satellite imagery. During this period, the SES band was found only between 30 and 31 January 2012 over the western Black Sea. This band maintained its dominance over the region for approximately 24 h. The cause and effects of this band and the precipitation that resulted were investigated. Meteorological data published by 12 airports, 16 meteorological stations and 5 radiosonde stations belonging to five countries were analysed within the two-day period to describe the relevant meteorological conditions. In addition, sea surface temperature data and synoptic charts of the upper atmospheric levels were investigated. According to the results, the maximum amount of snow (24 cm) was observed at the Inebolu Station (in Turkey). As a result of the effect of the vortex-type SES band moving over the Marmara and western Black Sea regions, a total of 102 flights belonging to a private airline company were cancelled, sea transportation was disrupted, and vehicular accidents occurred in Istanbul. In all radiosonde measurements, inversion layers were observed between the surface and the 700 hPa level, and wind direction changes occurred mostly between 0° and 50° within the same level range. The temperature difference between the sea surface and the 850 hPa level reached 25.8 °C where the vortex-type SES band core was located. In the synoptic level charts, the dominance of a low-pressure centre during the two-day period was observed in the area where the vortex-type SES band was formed.